The Influence of Implementation of Internal Control to Quality of Services: The Influence of Implementation of Internal Control to Quality of Services - Bunga Indah Bayunitri; Yunita, Hanny; Sukma, Irene; Lasniroha, Tetty (International Asia Of Law and Money Laundering, 2025)
This study aims to determine the influence of the implementation of internal control to service quality. The method used in this research is descriptive quantitative method by collecting data through library research and field studies through distributing questionnaires. The sampling technique used in this research is the saturated sampling method with a sample of 35 respondents who are employees of the “Perusahaan Daerah Air Minum (PDAM) Tirtawening-Bandung” in sections in the General Division unit. Analysis of the data used is simple linear regression analysis at a significance level of 5%. Results of this study indicate that the implementation of internal control has an influence to service quality, while the magnitude of the influence of the implementation of internal control in improving service quality is in “Perusahaan Daerah Air Minum (PDAM) Tirtawening-Bandung” is 69.7%.